Foliar turnover rates in Finland - comparing estimates from needle-cohort and litterfall-biomass methods - Tupek, Boris; Mäkipää, Raisa; Heikkinen, Juha; Peltoniemi, Mikko; Ukonmaanaho, Liisa; Hokkanen, Tatu; Nöjd, Pekka; Nevalainen, Seppo; Lindgren, Martti; Lehtonen, Aleksi
2015